NUTRITIONAL STATUS OF CHILDREN AGED 24 TO 59 MONTHS IN SOME COMMUNES OF BAC KAN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the nutritional status of children aged 24–59 months in selected communes of Bac Kan Province in 2025.Subjects and Methods: A cross-sectional descriptive study was conducted among 883 children aged 24–59 months from 8 communes in Bac Kan Province. Nutritional status was assessed using weight-for-age Z-scores (WAZ), height-for-age Z-scores (HAZ), and weight-for-height Z-scores (WHZ) according to the WHO Child Growth Standards (2006). The prevalence of underweight, stunting, and wasting was determined.Results: The prevalence of underweight among children aged 24–59 months in the study sites of Bac Kan Province was 19.9%, while the prevalence of stunting and wasting was 27.9% and 2.8%, respectively. Overall, 66.4% of children had normal nutritional status (i.e., were not affected by any form of malnutrition). 17.8% of children had only one form of malnutrition, 15.1% experienced two concurrent forms of malnutrition, and 0.8% were affected by all three forms. The prevalence of underweight was highest among children aged 36–47 months (20.8%), whereas stunting was most prevalent among those aged 24–35 months (31.8%). No statistically significant differences in nutritional status were observed between boys and girls.Conclusion: Malnutrition among children aged 24–59 months remains a significant public health concern in the study sites of Bac Kan Province, with a relatively high prevalence. Effective interventions are needed to prevent and manage malnutrition in this age group.
Keywords: nutritional status; stunting; underweight; wasting; children aged 24–59 months; Bac Kan Province.